Realism - Relativism - Constructivism: Proceedings of the 38th International Wittgenstein Symposium in Kirchberg - Kanzian, Christian; Kletzl, Sebastian; Neges, Katharina; Mitterer, Josef (De Gruyter, 2017)
Values; truth; destruction; constructivism; non-dualism